Massive faecal impaction leading to abdominal compartment syndrome and acute lower limb ischaemia. (20th June 2018) - Ho, Simon; Krawitz, Russel; Fleming, Bill
Abstract : Abdominal compartment syndrome (ACS) is associated with significant morbidity and mortality requiring prompt treatment. We report a rare case of a 57-year-old man who developed acute lower limb ischaemia, severe metabolic acidosis and renal impairment from massive faecal impaction of unknown aetiology resulting in ACS causing occlusion of the right common iliac artery. This was treated with faecal disimpaction, which eventually resulted in slow but full recovery.